ВЗАЄМОДІЯ СИНЕРГЕТИКИ ТА ПЕДАГОГІКИ: ПРОБЛЕМИ ТА ПЕРСПЕКТИВИ - Кичкирук, Т. В. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
В статті розглядається сучасний перехідний стан педагогіки – від класичної до нелінійної таможливості плідного використання принципів синергетики для вирішення ряду педагогічнихпитань.Кичкирук Т.В. Взаимодействие синергетики и педагогики: проблемы и перспективы. Встатье рассматривается современное переходное состояние педагогики – от классической донелинейной, а так же возможности плодотворного использования принципов синергетики длярешения ряда педагогических вопросов.Ключевые слова: синергетика, нелинейное мышление, образование, педагогикаKichkiruk T.V. The interaction of synergetics and pedagogies: problems and perspectives. Themodern transition situation of pedagogics from classical to nonlinear and possibicities of effective use ofsynergetics principles for solution of pedagogical tasks are reviewed in the article.Key words: synergetics, non-cinear thinking, education, pedagogics